Changing in Fatigue Life of 300 M Bainitic Steel after Laser Carburizing and Plasma Nitriding - Abdalla, Antonio J. [UNESP]; Santos, Douglas [UNESP]; Vasconcelos, Getúlio; Baggio-Scheid, Vladimir H.; Silva, Deivid F. [UNESP] (EDP Sciences, 2018)
In this work 300M steel samples is used. This high-strength steel is used in aeronautic and aerospace industry and other structural applications. Initially the 300 M steel sample was submitted to a heat treatment to obtain a bainític structure. It was heated at 850 °C for 30 minutes and after that, cooled at 300 °C for 60 minutes. Afterwards two types of surface treatments have been employed: (a) using low-power laser CO2 (125 W) for introducing carbon into the surface and (b) plasma nitriding at a temperature of 500° C for 3 hours. After surface treatment, the metallographic preparation was carried out and the observations with optical and electronic microscopy have been made. The analysis of the coating showed an increase in the hardness of layer formed on the surface, mainly, among the nitriding layers. The mechanical properties were analyzed using tensile and fatigue tests. The results showed that the mechanical properties in tensile tests were strongly affected by the bainitic microstructure. The steel that received the nitriding surface by plasma treatment showed better fatigue behavior. The results are very promising because the layer formed on steel surface, in addition to improving the fatigue life, still improves protection against corrosion and wear.